2014
DOI: 10.12659/pjr.890809
|View full text |Cite
|
Sign up to set email alerts
|

The value of coronary artery calcium score assessed by dual-source computed tomography coronary angiography for predicting presence and severity of coronary artery disease

Abstract: SummaryBackgroundMeasuring coronary artery calcium score (CACS) using a dual-source CT scanner is recognized as a major indicator for assessing coronary artery disease. The present study aimed to validate the clinical significance of CACS in predicting coronary artery stenosis and its severity.Material/MethodsThis prospective study was conducted on 202 consecutive patients who underwent both conventional coronary angiography and dual-source (256-slice) computed tomography coronary angiography (CTA) for any rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Overall, there were great controversies in this regard. The results of two different studies from our region were not similar either [13,14]. Thus, we aimed to evaluate the usefulness of this score for predicting CAD, its severity and CAD-related risk factors in our population.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Overall, there were great controversies in this regard. The results of two different studies from our region were not similar either [13,14]. Thus, we aimed to evaluate the usefulness of this score for predicting CAD, its severity and CAD-related risk factors in our population.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors suggested that it could be a good predicting factor for mild to moderate stenosis [13]. Others have reported that it has insufficient predictive value [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations